2016
DOI: 10.21037/hbsn.2016.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency and microwave ablation in combination with transarterial chemoembolization induce equivalent histopathologic coagulation necrosis in hepatocellular carcinoma patients bridged to liver transplantation

Abstract: RFA and MWA in sequential combination with DEB-TACE, used as a bridge to LT, are equally efficacious at inducing HCC tumor coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…There was no statistical difference in complication rates (3% vs. 2%) . In contrast to Thornton et al , Vasnani also compared the efficacy of RFA and MWA in combination with transarterial chemoembolization (DEB‐TACE), demonstrating that both RFA and MWA in sequential combination with DEB‐TACE are equally efficacious at inducing HCC tumor coagulation . The authors assessed 42 patients who underwent combined therapy: 11 tumors (2.9 cm; range, 1.8–4.3) treated with DEB‐TACE/RFA and 40 tumors (mean, 2.4 cm; range, 1.1–5.4) with DEB‐TACE/MWA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistical difference in complication rates (3% vs. 2%) . In contrast to Thornton et al , Vasnani also compared the efficacy of RFA and MWA in combination with transarterial chemoembolization (DEB‐TACE), demonstrating that both RFA and MWA in sequential combination with DEB‐TACE are equally efficacious at inducing HCC tumor coagulation . The authors assessed 42 patients who underwent combined therapy: 11 tumors (2.9 cm; range, 1.8–4.3) treated with DEB‐TACE/RFA and 40 tumors (mean, 2.4 cm; range, 1.1–5.4) with DEB‐TACE/MWA.…”
Section: Discussionmentioning
confidence: 99%
“…Among all 51 tumors, mean tumor coagulation of 95.8% was found on the 36 complete response on imaging at liver transplantation (LT). No correlation was reported between tumor coagulation and initial tumor size or time interval to LT. No tumor seeding was demonstrated along the ablation tracts . Abdelaziz et al demonstrated that TACE‐MWA obtained better response rates than TACE‐RFA with tumor size of 3–5 cm, with no difference in survival rates .…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment sequencing might be more variable in clinical practice as some patients are bridged or downstaged towards potentially curative treatments. Moreover, a deteriorating liver function and/ or rapid tumor progression during therapy may limit the use of subsequent treatment options …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a deteriorating liver function and/ or rapid tumor progression during therapy may limit the use of subsequent treatment options. 8,17,18 In this study, we characterized a large cohort of 2101 patients with HCC based on a 15-year experience from a large referral center-Hannover Medical School, Germany. The aim of this study was to analyze initial treatments and treatment sequencing in regard to tumor burden and liver function at first diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the synergistic effect of DEB-TACE and RFA has a powerful anti-cancer effect[ 40 ]. It is demonstrated by the studies of patients with liver metastases from colorectal cancer from Lee et al[ 41 ] and Ahmed et al[ 42 ].…”
Section: Discussionmentioning
confidence: 99%